745. Combination Treatment of Liposomal Amphotericin B and Isavuconazole is Synergistic in Treating Experimental Mucormycosis - Gebremariam, Teclegiorgis (Open Forum Infect Dis, 2020)
BACKGROUND: Mucormycosis is a life-threatening infection that predominantly occurs in immunocompromised hosts. Liposomal amphotericin B (L-AMB) and isavuconazole (ISAV) are commonly used antifungal drugs to treat mucormycosis. However, the efficacy of combination therapy of L-AMB + ISAV compared to monotherapy is unknown. We used an immunosuppressed mouse model of pulmonary mucormycosis to compare the efficacy of L-AMB + ISAV vs. either drug alone. METHODS: ICR mice were immunosuppressed with cyclophosphamide (200 mg/kg) and cortisone acetate (500 mg/kg) on Days -2, +3, and +8 relative to intratracheal infection with 2.5 x 10(5) cells of Rhizopus delemar 99-880, or 2.5 x 10(6) cells of Mucor circinelloides. Treatment with L-AMB (10 mg/kg, given intravenously qd), ISAV (56 mg/kg, by oral gavage TID), or a combination of both started 8 h post-infection and continued through day +4. Placebo mice received vehicle control. Survival studies through day +21 and tissue fungal burden (by conidial equivalent [CE] using qPCR) on Day +4, served as primary and secondary endpoints. RESULTS: For mice (n=20) infected with R. delemar, L-AMB and ISAV equally prolonged median survival time and enhanced survival vs. placebo (19 and 16 days for L-AMB and ISAV, respectively, and overall survival of 50% for either drug alone, vs. 9 days and 5% overall survival for placebo, P< 0.002 for either drug vs. placebo by Log Rank test). Importantly, combination treatment enhanced median survival time (>21 days) and resulted in an overall survival of 80% (P< 0.05 vs. all treatments). Both antifungal drugs reduced tissue fungal burden of mice (n=10) lungs and brain by ~1.0-2.0 log vs. placebo-treated mice (P< 0.02 by Wilcoxon Rank Sum). Consistent with the survival data, treatment with combination therapy resulted in 2.0-3.5 log reduction in fungal burden of either organ vs. placebo and 1.0 log reduction vs. either drug alone (P< 0.005). Similar results were obtained using mice infected with M. circinelloides. CONCLUSION: L-AMB + ISAV demonstrate greater activity vs. monotherapy treatment in immunosuppressed mice infected with either of two common causes of mucormycosis. These studies warrant further investigation of LAmB + ISAV combination therapy as an optimal therapy of human mucormycosis. DISCLOSURES: Therese Kitt, MD, Astellas Pharma (Employee) Ashraf S. Ibrahim, PhD, Astellas Pharma (Research Grant or Support)